Congenital extranasal glial heterotopia in infancy: a rare case report - Jain, Preeti; Mulla, Arsala; Yadav, Mamta; R., Pradeep (International Journal of Research in Medical Sciences, 2026)
A seven-month-old female child has been presented with extra nasal mass on the dorsum of the nasal bridge since birth. On clinical examination a 1.6x1.4 cm globular, firm, non-compressible, non-pulsatile mass was noted over the nasal dorsum, slightly left of midline. Radiological studies were suggestive of extranasal glioma without intranasal or intracranial extension. Histopathological examination revealed a non-encapsulated, ill-defined lesion composed of sheets and nests of benign and mature glial tissue. Glial heterotopia is defined as the mass of mature brain tissue isolated from the cranial cavity or spinal canal. Nasal glial heterotopias are congenital tumors. The nose and nasopharynx are the most common sites of location. Nasal glial heterotopias are rare benign lesions that can be challenging to diagnose clinically and radiologically due to their uncommon presentation. In this case report; we discuss a rare case of extranasal glial heterotopia, highlighting its clinical presentation, diagnostic challenges, radiological and histopathological features.